Postpartum takotsubo cardiomyopathy complicated with severe pulmonary edema and cardiogenic shock – a case report - Bembey, Raghavi Abhilesh; Jha, Rajesh Ranjan (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Takotsubo cardiomyopathy (TCM) is a rare but life-threatening illness that can affect middle aged, young and pregnant women. It is a cardiac emergency and can mimic many other life threatening conditions like myocardial infarction, acute myocarditis, peripartum cardiomyopathy or dilated cardiomyopathy and is diagnosed by exclusion. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. Here we report a rare case of takotsubo cardiomyopathy in a young 28 year old female immediately post vaginal delivery of her normal full term twin pregnancy, who was otherwise a healthy female. She went on to develop complication of left ventricular heart failure and cardiogenic shock, which were successfully managed by conservative treatment leading to a full recovery. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Takotsubo or stress cardiomyopathy is a rare entity and often a missed diagnosis, which if caught on time and treated leads to great prognosis. Our patient made a full recovery and is living a healthy life.